(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3GdMeO ddg TcQkG Ydi fhGdg CeG HYO aEfi bO ChOYJ HgPG GdcJGH eG UM YfOi ef gPg GddZI HGH GdCda GdegehR ef cJGH GdUMGM s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg hUd GddGe dPP GddPI hGMO ef GddPGJ dhP hde JWdH GdNjQ GdedGhP ef YeQh hfYfi Gdbdjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1071s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GddZIs